2014
DOI: 10.3748/wjg.v20.i14.4093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precut sphincterotomy on post-endoscopic retrograde cholangiopancreatography pancreatitis: A systematic review and meta-analysis

Abstract: Early precut technique for common bile duct cannulation decreases the trend of post-ERCP pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 25 publications
1
41
0
2
Order By: Relevance
“…38 Subgroup analysis of a meta-analysis revealed that NKF significantly decreased the risk of PEP (OR, .27; 95% CI, .09-.82) with an absolute risk reduction of 5% (95% CI, 1%-10%), whereas NKP did not (OR, .89; 95% CI, .41-1.92). 34 In a retrospective study NKF had a lower PEP rate than the others; the PEP rates of NKF, NKP, and TPS were 2.6%, 21%, and 22.4%, respectively (P Z .001). 40 Therefore, if the pancreatic duct can be cannulated, a pancreatic stent should be placed before NKP to guide the precut and to reduce PEP risk; a retrospective study showed that precutting over a pancreatic stent achieved a higher success rate and a lower adverse event rate.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…38 Subgroup analysis of a meta-analysis revealed that NKF significantly decreased the risk of PEP (OR, .27; 95% CI, .09-.82) with an absolute risk reduction of 5% (95% CI, 1%-10%), whereas NKP did not (OR, .89; 95% CI, .41-1.92). 34 In a retrospective study NKF had a lower PEP rate than the others; the PEP rates of NKF, NKP, and TPS were 2.6%, 21%, and 22.4%, respectively (P Z .001). 40 Therefore, if the pancreatic duct can be cannulated, a pancreatic stent should be placed before NKP to guide the precut and to reduce PEP risk; a retrospective study showed that precutting over a pancreatic stent achieved a higher success rate and a lower adverse event rate.…”
mentioning
confidence: 92%
“…33 Another meta-analysis showed that the ORs of PEP for using the precut technique immediately and within 5 or 10 minutes of standard cannulation were .73 (95% CI, .23-2.33), .85 (95% CI, .40-1.80), and .55 (95% CI, .29-1.03), respectively. 34 In terms of PEP, 10 minutes appears to be the optimum time allowed for the standard cannulation technique before considering the use of precut technique. Notably, precut technique requires expertise and is associated with a higher risk of adverse events, particularly perforation and bleeding, when performed by low-volume endoscopists.…”
mentioning
confidence: 99%
“…TPS technique is a relatively new precut technique among the various precut techniques, which was first described in 1995. Previous studies have found that TPS is a safe and effective procedure in patients with difficult bile duct access . However, the use of the precut technique for achieving deep cannulation of the bile duct is not recommended for inexperienced endoscopists as it is claimed to increase post‐ERCP complications …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that TPS is a safe and effective procedure in patients with difficult bile duct access. 24 However, the use of the precut technique for achieving deep cannulation of the bile duct is not recommended for inexperienced endoscopists as it is claimed to increase post-ERCP complications. 25 Compared to standard cannulation, DWT may replace standard cannulation or become the salvage procedure in cases of unsuccessful biliary cannulation as a result of its high success rate with an acceptable incidence of PEP.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, "moving" the precut technique earlier during a difficult cannulation has been associated with a decreased risk of PEP [13]. Moreover, PF compared to conventional precut technique significantly decreased the PEP rate in a systematic metaanalysis [14]. The most reasonable explanation is that during conventional precut, the pancreatic orifice is not protected and injuries may occur.…”
mentioning
confidence: 99%